Acehnese Dance: Its Application to Early Childhood Kinesthetic Intelligence - Ula, Zahratul; Zulfitri, Zulfitri; Veryawan, Veryawan (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
The problem in this research is that children learn dance from teachers who are not competent in their field and do not have experience with the Aceh Bungong Jeumpa dance both in terms of theory and practice. Teachers who teach have a sports education background. The teacher only shows the Aceh Bungong Jeumpa dance movements via video to the children but does not mention the names of the movements used. This research aims to describe Acehnese dance in terms of its application to the Kinesteric Intelligence of Early Childhood. Researchers use qualitative methods to collect the data needed by researchers using interviews, observation, and documentation techniques. The results of the research stated that 1) The implementation of Acehnese dance learning in the Pembina Simpang Ulim Kindergarten was carried out when the farewell events at school were approaching. Dance learning is not focused as a subject or only as an activity held when a farewell event is approaching, so in art lessons, teachers only focus on singing activities accompanied by movements that are expected to provide joy to children. 2) The application of Acehnese dance learning to improve the kinesthetic intelligence of early childhood at the Pembina Simpang Ulim State Kindergarten, researchers observed through observation sheets that the researchers carried out for three cycles. In cycle I, children also have not yet memorized the rhythm of the song Bungong Jeumpa so it is still difficult to direct children to follow the movements that are conveyed during the dance activities taught. In cycle II, several obstacles were still encountered, such as children still not focusing enough on learning the dance taught by the teacher, then children still not memorizing the movements according to the bungong jump dance. Meanwhile, in cycle III, children can follow the Acehnese dance movements according to the directions given by the teacher. Therefore, this research is considered successful and there is no need to carry out teaching in the next cycle.